ARTERIAL STIFFNESS AND CARDIOVASCULAR RISK FACTORS IN YOUNG MEN (41-44 YEARS) - O. Yu. Isaykina; V. B. Rozanov; E. Yu. Zvolinskaya; H. S. Pugoeva; A. A. Alexandrov (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the relationship of individual cardiovascular risk factors with arterial stiffness and subclinical atherosclerosis in young men.Material and methods. The study is part of a 32-year prospective cohort monitoring of males, beginning with childhood (11-12 years). The study-included 303 (30.1%) representatives of the initial population sample aged 41-44 who underwent an outpatient examination at the State Research-Center for Preventive Medicine in 2015-2016. The examination included a survey by a standard questionnaire, measurement of anthropometric parameters, blood pressure (BP), pulse counting. Biochemical assays were carried out according to standard laboratory procedures. Applanation tonometry-was used to measure stiffness of the arterial wall. Intima-media thickness (IMT) and subclinical atherosclerosis signs were determined in both left and right carotid arteries by ultrasound scanning.Results. Arterial stiffness and central pressure were significantly higher in the group with hypertension (HT). Risk of HT development depended on HT-presence in mother and did not depend on HT in father. HT was associated with obesity (79.4% vs 44.3%; p<0.001), especially of abdominal type and elevated triglycerides (1.3±0.9 vs 1.8±1.1 mmol/l; p<0.05), this indirectly reflected nutritional disorder and development of metabolic syndrome. The analysis of arterial stiffness parameters showed positive correlation with mean systolic (r=0.256) and diastolic (r=0.228) BP in the brachial artery and also with heart rate (r=0.133). A statistically significant positive correlation of central pressure in the aorta and pulse BP with indices of arterial-stiffness was noted. When comparing arterial stiffness and duplex scans, a correlation of mean IMT with the augmentation index (r=0.131) and augmentation BP (r=0.125) was obtained, but no correlation between IMT and pulse wave velocity was found. Correlation of vascular rigidity with total cholesterol level was also noted (r=0.121).Conclusion. The arterial stiffness was closely related to HT and already developed in early stages, in a fairly young age. Arterial stiffness in men was not associated with dyslipidemia and diabetes presence. Interrelation of arterial stiffness and degree of early atherosclerotic vascular lesions was ambiguous.